Does the Government have the authority to annul Regional Regulations? - Sukardi, Sukardi; Wardana, Dodi Jaya (Faculty of Law, University of Muhammadiyah Malang, 2024)
The existence of a dualism in the authority to annul Regional Regulations by the Supreme Court through judicial review and by the Government through executive review has been a significant issue. However, through the Constitutional Court Decisions Number 137/PUU-XIII/2015 and Number 56/PUU-XIV/2016, the Government's authority to annul Regional Regulations has been revoked, transferring this authority to the Supreme Court. This article discusses the ratio decidendi of the Constitutional Court decisions regarding the authority to annul Regional Regulations and the implications of these decisions on the mechanism for supervising Regional Regulation. This normative juridical research employs conceptual, case, and statutory approaches. The analysis shows that the decisions of the Constitutional Court Numbers 137/PUU-XIII/2015 and 56/PUU-XIV/2016 led to a significant reduction in the quality and execution power of the Supreme Court decisions concerning judicial reviews, creating potential policy conflicts between central and regional governments, and between petitioners and local governments, and hindering the supervision of Regional Regulations due to the Supreme Court's reactive nature in awaiting applications.